PENGARUH MODEL PEMBELAJARAN KOOPERAKTIF TYPE TAI (TEAM ASSISTED INDIVIDUALIZATION) TERHADAP HASIL BELAR SISWA KELAS X SMA NEGERI 10 LUWU - eva sohriati; Fitrah Al anshori; Febi Febrianti; Nurasia (Jurnal Biogenerasi, 2022)
This study aims to determine the effect of the cooperative learning model type TAI (Team Assisted Individualization). Against the Learning Outcomes of Class X SMAN 10 Luwu Students. The type of research used is experimental research with a quasi-experimental design and the design is non-equivalent control group design. The instrument used in this study was a test of student learning outcomes (pretest and posttest). The research samples taken were students of class X MIPA 1 and class X MIPA 2 SMAN 10 Luwu in the 2021 academic year with a total of 60 students. Sampling was used by purposive sampling technique. The data analysis technique used is descriptive and inferential statistics. From the results of descriptive analysis, the average value of student learning outcomes in class X MIPA 2 SMAN 10 Luwu by applying the cooperative learning model type TAI (Team Assisted Individualization) obtained 80.50 in the high category. The results of the inferential analysis on student learning outcomes using the samplet-test test obtained a value of Sig. (2-tailed) of 0.000 <0.05, it was concluded that there was an effect on the treatment using a cooperative learning model type TAI (Team Assisted Individualization) increasing results student learning in the overall sample population.